Desarrollo de la hipertrofiasarcoplasmática de los cuádriceps, mediante cargas ondulatorias en la disciplina de físico-culturismo. - Amaguaya Moyón, Franklin Ricardo (2017)
The present research work called "Development of sarcoplasmic hypertrophy of the quadriceps, by wave loads in the discipline of physical-bodybuilding" responds to a type of experimental research where the main objective is to determine the effectiveness of this method in relation to the traditional methodologies. The study involved two experimental and control study samples with participants aged between 18 and 37 years. The instrument used for the evaluation of hypertrophic volume was the measurement of the quadriceps perimeters in the stopped position. The proposed program was formed by the application of 4 planned exercises between 50% and 100% loads in relation to the 1RM of each one, methodology applied during 9 weeks with 3 trainings in each of them. In the inter group comparison, the experimental group presented improvements at the quadriceps level of P <0.001 (0.004), while the control group did not show improvement, resulting in P> 0.05 (0.058). After the application of the non-parametric Wilcoxon statistical test for independent samples, it was determined that in the experimental group there was a significant difference in a level of P <0.05, in relation to the control group that determined a P value ˃ 0 , 05, evidencing the efficacy of the wave method on the traditional method in the development of sarcoplasmic hypertrophy.